Extension and University Management: A Study of Project Chiquitos in Chiquitania, Bolivia [Extenso e Gesto Universitária: Um estudo do Projeto Chiquitos na Chiquitania Boliviana] - Santos Delgado, A. (2017)
This article aims to contextualize the project Chiquitos in Chiquitania, Bolivia from the perspective of University Extension and Management. This project, proposed by the Universidad Técnica Particular de Loja (Ecuador) and the Universidade Católica Boliviana "San Pablo", in Chiquitos (Bolivia) aims to disseminate research and encourage the development of a remote and socially deprived region through technologically appropriate environments. Through a systematic literature review, we intend to discovery the existing publications of "University Extension and Management" that are convergent with the main focus. For a selection of articles we used the Scopus database from which, after reading the summaries of 10 records selected, there was a selection for adherence to the research question and identified four articles that comprise the study sample. After the analysis of these articles, it can be stated that there is a convergence between the Project and the Chiquitos literature reports regarding the role of the university from the perspective of social responsibility and commitment to quality of education also aimed at meeting the needs and challenges of society.